1952
DOI: 10.1152/ajplegacy.1952.170.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adrenal Medullary Hormones on Renal Excretion of Water and Electrolytes

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1954
1954
1981
1981

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Their administration caused diuresis in rabbits (32,33) and rats (34)(35)(36), and either diuresis or antidiuresis in dogs (37)(38)(39). Epinephrine and norepinephrine also can produce either effect (32,(40)(41)(42)(43)(44)(45). In all these, as well as in our own experiments, the circumstances that dictate one effect rather than the other remain unclear.…”
Section: Discussionmentioning
confidence: 64%
“…Their administration caused diuresis in rabbits (32,33) and rats (34)(35)(36), and either diuresis or antidiuresis in dogs (37)(38)(39). Epinephrine and norepinephrine also can produce either effect (32,(40)(41)(42)(43)(44)(45). In all these, as well as in our own experiments, the circumstances that dictate one effect rather than the other remain unclear.…”
Section: Discussionmentioning
confidence: 64%
“…Gross & Schneider (95) reported that epinephrine and norepinephrinf. In saline-loaded rats norepinephrine increased the urine flow while epinephrine reduced it (69) . It is suggested that epinephrine releases a sub stance in the spleen with norepinephrine-like actions.…”
Section: Peripheral Visceral Efferent System Thoracolumbar Outflowmentioning
confidence: 87%
“…Eversole, Giere & Rock (1952) found that noradrenaline caused an increase of glomerular filtration rate and also an apparent decrease in tubular reabsorption of water. Glomerular filtration rate is also likely to increase with diuretic amounts of adrenaline and bretylium.…”
Section: Discussionmentioning
confidence: 99%